Inflammatory Bowel Disease: An Overview of Immune Mechanisms and Biological Treatments - Bruno Rafael Ramos de Mattos; Maellin Pereira Gracindo Garcia; Julia Bier Nogueira; Lisiery Negrini Paiatto; Cassia Galdino Albuquerque; Caique Lopes Souza; Luís Gustavo Romani Fernandes; Wirla Maria da Silva Cunha Tamashiro; Patricia Ucelli Simioni (Mediators of Inflammation, 2015)
Inflammatory bowel diseases (IBD) are characterized by chronic inflammation of the intestinal tract associated with an imbalance of the intestinal microbiota. Crohn’s disease (CD) and ulcerative colitis (UC) are the most widely known types of IBD and have been the focus of attention due to their increasing incidence. Recent studies have pointed out genes associated with IBD susceptibility that, together with environment factors, may contribute to the outcome of the disease. In ulcerative colitis, there are several therapies available, depending on the stage of the disease. Aminosalicylates, corticosteroids, and cyclosporine are used to treat mild, moderate, and severe disease, respectively. In Crohn’s disease, drug choices are dependent on both location and behavior of the disease. Nowadays, advances in treatments for IBD have included biological therapies, based mainly on monoclonal antibodies or fusion proteins, such as anti-TNF drugs. Notwithstanding the high cost involved, these biological therapies show a high index of remission, enabling a significant reduction in cases of surgery and hospitalization. Furthermore, migration inhibitors and new cytokine blockers are also a promising alternative for treating patients with IBD. In this review, an analysis of literature data on biological treatments for IBD is approached, with the main focus on therapies based on emerging recombinant biomolecules.